1995
DOI: 10.1037/0278-6133.14.6.570
|View full text |Cite
|
Sign up to set email alerts
|

Validation of measures of condom and other contraceptive use among women at high risk for HIV infection and unitended pregnancy.

Abstract: This study assessed the applicability of the transtheoretical model of behavior change (J.O. Prochaska & C.C. DiClemente, 1983, 1984) to the measurement of contraceptive use among 296 women at high risk for HIV infection and transmission. Structural equation modeling suggested that a measure of general contraceptive use could be used to assess use of oral contraceptives and hormonal implants but that measurement of condom use required separate assessments for main and other partners. Self-efficacy (SE) and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 38 publications
10
99
2
Order By: Relevance
“…As with other studies, 16,18,[22][23][24] participants in our study were more likely to engage in consistent condom use with their other partners and less likely to engage in consistent condom use with their main partners. Given that the resources needed to conduct interventions (e.g., money, time, personnel) are finite, knowing that differences exist between stage distributions for main and other partners could help an interventionist working with this study's population set priorities for interventions according to clients' needs and resource availability.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…As with other studies, 16,18,[22][23][24] participants in our study were more likely to engage in consistent condom use with their other partners and less likely to engage in consistent condom use with their main partners. Given that the resources needed to conduct interventions (e.g., money, time, personnel) are finite, knowing that differences exist between stage distributions for main and other partners could help an interventionist working with this study's population set priorities for interventions according to clients' needs and resource availability.…”
Section: Discussionsupporting
confidence: 66%
“…The rationale for having separate staging algorithms to assess condom use by specific partner type is based on prior research, which has shown that main and other partner relationships are qualitatively different, and that individuals are at different stages of readiness to use condoms based on the partner type. 14,18 Each study participant was classified into one of the five stages based on the individual's responses to the staging items. Individuals were classified as being in (1) maintenance, if for 6 months or more they had been using condoms every time they had sex; (2) action, if they had been using condoms every time, but for less than 6 months; (3) preparation, if they planned to use condoms in the next 30 days every time and were using condoms almost every time they had sex during the past 6 months; (4) contemplation, if they planned to start using condoms every time they had sex sometime in the next 6 months; and (5) precontemplation, if they did not plan to start using condoms every time they had sex in the next 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once people are ready for change, the positive/negative attitude ratio reverses (Prochaska, 1994). However, studies on condom use readiness have demonstrated that, even for people who were condom users, their negative attitudes towards using condoms did not decease as much as findings observed for other behaviors (Bowen & Trotter, 1995;Galavotti et al, 1995;Grimley et al, 1992).…”
Section: Introductionmentioning
confidence: 92%
“…If a change has been maintained for more than six months, individuals' behaviors are classified as (5) the maintenance stage (M) (DiClemente, 1993;Prochaska & DiClemente, 1984;Prochaska, DiClemente, & Norcross, 1992). The stages of change have been used to assess a variety of behaviors, including initiation of condom use in a general population (Galavotti et al, 1995;Grimley et al, 1992;Grimley, Prochaska, Velicer, & Prochaska, 1995;Noar, Morokoff, & Redding, 2002;Prochaska, Redding, Harlow, Rossi, & Velicer, 1994) and condom use among injection drug users and crack cocaine smokers (Anderson et al, 1996;Bowen & Trotter, 1995;Rhodes & Malotte, 1996;Sagrestano, Rogers, Kittleson, & Sarvela, 2005;Stark et al, 1998;Timpson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%